Chronic treatment with carvacrol improves passive avoidance memory in a rat model of Parkinson's disease - Hossein Haddadi; Ziba Rajaei; Hojjatallah Alaei; Somayeh Shahidani (Arquivos de Neuro-Psiquiatria)
ABSTRACT The present study investigated the effects of carvacrol on motor and memory deficits as well as hyperalgesia in the 6-OHDA-lesioned rat model of Parkinson's disease. The animals were subjected to unilateral microinjection of 6-OHDA into the medial forebrain bundle and treated with carvacrol (25, 50 and 100 mg/kg, ip) for six weeks after surgery. The 6-OHDA-lesioned rats showed contralateral rotations towards the lesion side, which was accompanied by learning and memory deficits in a passive avoidance test and a decrease in tail withdrawal latency in a tail flick test at the end of week 6. The results also showed that treatment with carvacrol at a dose of 25 mg/kg ameliorated memory deficits, with no effect on rotations and hyperalgesia in lesioned rats. In conclusion, carvacrol improves memory impairments in rats with Parkinson's disease; therefore, it may serve as an adjunct therapy for the alleviation of memory deficits in Parkinson's disease patients.